2012
DOI: 10.1111/j.1365-2664.2012.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape simplification and altitude affect biodiversity, herbivory and Andean potato yield

Abstract: Summary1. The simplification of agricultural landscapes through the increase in cropped area has caused the loss of habitats for many species that fulfil important ecosystem services such as pest control and production. Evidence for detrimental effects on ecosystem services is scarce, particularly in tropical regions. 2. We studied the effect of the percentage of cropped land in the landscape and altitude in tropical agro-ecosystems in relation to crop pest regulation and yield. In the Colombian Andes, we esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 41 publications
1
50
2
2
Order By: Relevance
“…We chose to measure these landscape metrics because previous studies have shown that they could affect the dynamics and distribution of lepidopteran pests (Poveda et al. ), aphids (Woltz et al. ) and flea beetles (Banks , Andersen et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to measure these landscape metrics because previous studies have shown that they could affect the dynamics and distribution of lepidopteran pests (Poveda et al. ), aphids (Woltz et al. ) and flea beetles (Banks , Andersen et al.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, far fewer studies have evaluated the effects of such pest–natural‐enemy complexities on crop yield (but see Poveda et al. , Liere et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing problem of pests and diseases experienced by farmers is associated with rising temperatures and further exacerbated by shifts towards monoculture, pest-susceptible varieties, and abbreviated crop rotation schedules (Parsa 2010;Perez et al 2010;McDowell and Hess 2012;Poveda et al 2012). Adaptation actions reported in our study communities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that landscape changes and climate changes would be related to pest damage, based on the hypothesis that crop simplification and global warming would affect biological control agents (Zhao et al, 2015b;Poveda et al, 2012). Based on the resource concentration hypothesis and habitat management, it was hypothesized that (i) landscape change and climate change would have a great effect on pest damage, and pest damage would increase with increasing landscape simplification and global warming, and (ii) landscape change would be the key driving factor and would have a greater influence on pest damage than climate change due to the polydirectional temperature fluctuations during the past 60 years in China (Figure 1).…”
Section: Introductinmentioning
confidence: 99%